2023
DOI: 10.1177/14779714231157248
|View full text |Cite
|
Sign up to set email alerts
|

The role of locus of control in mediating the relationship between nontraditional factors and academic entitlement

Abstract: The current study further explored the relationship between nontraditional students and academic entitlement. Previous research has established that the presence of more nontraditional factors predicts lower levels of reported academic entitlement. The mechanisms responsible for this connection have not been explored though. The current study examined the impact of locus of control on the relationship between nontraditional factors and academic entitlement. Participants ( N = 332) were asked to report their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The overprotective parenting style over-controls the a child’s daily behaviors and activities, restricting the children for long periods of time and conditioning them to listen to others’ opinions rather than forming their own, thus forming a high sense of external control 35 . Previous studies have shown that parental over-protection is positively correlated with a child’s sense of external control 36 , 37 , external control significantly predicts academic entitlement 29 – 31 , parental over-protection has a positive impact on academic entitlement 26 . Therefore, external control may play a mediating role in the impact of parental over-protection on academic entitlement.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The overprotective parenting style over-controls the a child’s daily behaviors and activities, restricting the children for long periods of time and conditioning them to listen to others’ opinions rather than forming their own, thus forming a high sense of external control 35 . Previous studies have shown that parental over-protection is positively correlated with a child’s sense of external control 36 , 37 , external control significantly predicts academic entitlement 29 – 31 , parental over-protection has a positive impact on academic entitlement 26 . Therefore, external control may play a mediating role in the impact of parental over-protection on academic entitlement.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, they place strict demands on teachers and schools as being responsible for them achieving well academically. Previous studies have shown that external control significantly predicts academic entitlement 29 – 31 . The formation and development of locus of control is not greatly influenced by congenital genetics; rather, the family environment has been shown to be the main influencing factor 32 .…”
Section: Introductionmentioning
confidence: 95%